2019
DOI: 10.1111/aas.13532
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation in patients at risk for cervical spinal cord injury: A systematic review

Abstract: Background: Tracheal intubation in patients at risk for secondary spinal cord injury is potentially difficult and risky. Objectives: To compare tracheal intubation techniques in adult patients at risk for secondary cervical spinal cord injury undergoing surgery. Primary outcome was firstattempt failure rate. Secondary outcomes were time to successful intubation and procedure complications. Design: Systematic review and meta-analysis of randomized controlled trials (RCTs) with trial sequential analysis (TSA). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This was in part due to the ability to undertake this with the patient awake, thereby allowing neurological assessment after tracheal intubation and before induction of general anaesthesia. A systematic review from 2019 was unable to identify any study that had compared awake vs. non‐awake tracheal intubation [28]. A more recent randomised controlled trial compared awake tracheal intubation in patients with upper cervical spine instability using a flexible bronchoscope with the McGrath videolaryngoscope [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was in part due to the ability to undertake this with the patient awake, thereby allowing neurological assessment after tracheal intubation and before induction of general anaesthesia. A systematic review from 2019 was unable to identify any study that had compared awake vs. non‐awake tracheal intubation [28]. A more recent randomised controlled trial compared awake tracheal intubation in patients with upper cervical spine instability using a flexible bronchoscope with the McGrath videolaryngoscope [29].…”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis identified nine studies that reported neurological complications after tracheal intubation in patients at risk of cervical cord injury (definitions varied between different studies) [28]. Overall, there were 4/1177 (0.34%) cases of postoperative neurological deterioration: one case involved upper limb numbness which spontaneously resolved; and there were no details provided as to the nature, severity and duration of the symptoms for the other cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of anesthesia: Patients in both groups were induced by intravenous injection of midazolam sufentanil , rocuronium bromide and etomidate emulsion. After the muscle relaxant completely had taken effect on the epiglottis root and surface anesthesia was performed, the enhanced tracheal tube was inserted in the neutral position under the visual laryngoscope [5] . After successful intubation, the anesthesia machine was connected, and the tidal volume and respiratory rate were adjusted according to P ET CO 2 .…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
“…3 Lower respiratory tract infections are usually caused by bacteria and viruses. 4,5 The wide application of antibacterial drugs has changed the types of pathogenic bacteria that can invade the lower respiratory tract; the number of drugresistant pathogen strains has gradually increased together with the level of drug resistance, and multidrug-resistant strains have appeared, bringing great challenges to clinical treatment. 6 In recent years, with accelerated growth of the global aging population, the number of older patients undergoing surgical treatment has been increasing each year.…”
Section: Introductionmentioning
confidence: 99%